ANALYSIS OF TOMATO DATES BUSINESS DEVELOPMENT STRATEGIES USING BUSINESS MODEL CANVAS APPROACH AND SWOT-ANP - Talitha Dea Azzaria; Wendra Gandhatyasri Rohmah; Panji Deoranto; Riska Septifani; Dhita Morita Ikasari (Fakultas Teknologi Pertanian Universitas Brawijaya, 2022)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in developing the national economy. CV Firman SK is one of the MSMEs engaged in agroindustry located in Malang regency. CV Firman SK faced a revenue decline problem because of the covid-19 pandemic. Tomato dates are one of the superior products that experienced the most significant decrease in revenue compared to other products, which is a 50% revenue decrease. This research aims to determine the priority order of business development strategy. The methods used in this study are the BMC approach and integration of SWOT-ANP. The BMC approach maps the business model of CV Firman SK. The business model will be the basis for establishing alternative strategies using SWOT analysis. SWOT methods are integrated with ANP methods to make accurate priorities of business development strategies. The result showed that the highest priority and most recommended alternative strategy is the SO1 strategy, with a score of 0.350. Elements of BMC that need to be improved based on business development alternative strategies are channels, key partnerships, and value propositions. CV Firman SK is advised to implement a proposed business development strategy based on the order of the most prioritized strategies.